2020
DOI: 10.3389/fmicb.2020.01671
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Characterization of Indoor Dust Bacterial and Fungal Microbiota in Homes of Asthma and Non-asthma Patients Using Next Generation Sequencing

Abstract: Background: The exposure of house occupants to indoor air pollutants has increased in recent decades. Among microbiological contaminants, bacterial and fungal aerosols remain poorly studied and the debate on the impact of these aerosols on respiratory health is still open. This study aimed to assess the diversity of indoor microbial communities in relationship with the health of occupants. Methods: Measurements were taken from dwellings of 2 cohorts in Brittany (France), one with children without any pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…We observed the same dominant classes in our study, in addition to Eurotiomycetes (including the major filamentous fungal genera Aspergillus and Penicillium), and the likely human-associated yeast family Malasseziomycetes. The fungal composition was dominated by two phyla, Ascomycota and Basidiomycota, as has been observed in previous studies (Hanson et al, 2016;Gangneux et al, 2020). In our study, we saw on average a near equal divide between Basidiomycota and Ascomycota, while Hanson et al (2016) reported an Ascomycota-dominated composition from settled dust (vacuumed).…”
Section: Discussionsupporting
confidence: 89%
“…We observed the same dominant classes in our study, in addition to Eurotiomycetes (including the major filamentous fungal genera Aspergillus and Penicillium), and the likely human-associated yeast family Malasseziomycetes. The fungal composition was dominated by two phyla, Ascomycota and Basidiomycota, as has been observed in previous studies (Hanson et al, 2016;Gangneux et al, 2020). In our study, we saw on average a near equal divide between Basidiomycota and Ascomycota, while Hanson et al (2016) reported an Ascomycota-dominated composition from settled dust (vacuumed).…”
Section: Discussionsupporting
confidence: 89%
“…Older studies using culture methods on air and dust samples reported fungal identity at the genus or species group level (e.g., Penicillium or Aspergillus/Penicillium group) [10][11][12]. Newer studies using next-generation sequencing on dust and swab samples reported fungal identity at the genus level [13], but mostly at the order or class level (e.g., Eurotiales or Eurotiomycetes) [14][15][16], or even at the phylum level [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these molds are non-pathogenic, their detection showed a lack of effective filtration or cleaning and/or the existence of conditions that favor the settling of molds, including Aspergillus [ 20 ]. Furthermore, culture isolation focuses on the presence of particular fungi, and molecular methods such as next generation sequencing, are reliable tools for identifying and tracking the fungal diversity of indoor air [ 21 ]. Finally, some variables that could have influenced the results of air samples including seasons, weather, and work progress [ 22 ] were not considered in this study.…”
Section: Discussionmentioning
confidence: 99%